Element determination on slice sediment sequences of IODP Site 363-U1489 - Haowen Dang (PANGAEA, 2021)
This dataset contains the major, trace and rare earth elemental data of the siliciclastic particles along the upper ~84 m on-slice sediment sequence of IODP Site U1489 (02°07.19'N, 141°01.67'E; 3421 m water depth). The sampling interval is about 50 cm, approximately equivalent to a time-resolusion of ~15-42 ka.